Pectin extraction from nephelium lappaceum (binjai variety) peel using pulsed electric field - Ganes Aurora Santoso; Luqman Agung Wicaksono; Muhammad Alfid Kurnianto; Hadi Munarko; Andre Yusuf Tisna Putra; Anugerah Dany Priyanto (Konversi, 2025)
This study aims to evaluate the effects of electric field intensity, extraction time, and solvent ratio on pectin yield from binjai rambutan skin using Pulsed Electric Field (PEF). The One Factor at a Time (OFAT) method was applied in three stages: (1) determining the optimal electric field intensity (5, 10, 15, and 20 kV/cm) with a fixed extraction time of 15 minutes and a solvent ratio of 1:30 w/v; (2) assessing the effect of extraction time (5, 10, 15, and 20 minutes) while maintaining the selected electric field intensity and a solvent ratio of 1:30 w/v; and (3) evaluating the influence of different solvent ratios (1:20, 1:30, 1:40, and 1:50 w/v) using the selected electric field intensity and solvent ratio from the previous stages. Each stage was conducted in duplicate to ensure data reliability. The collected data were analyzed using Analysis of Variance (ANOVA), followed by the Duncan Multiple Range Test (DMRT) at a 95% confidence level with SPSS v.27.0.1 software. The results demonstrate that each of electric field intensity, extraction time, and solvent ratio influence pectin yield. The optimal conditions obtained were an electric field intensity of 20 kV/cm, yielding 3.41%; an extraction time of 10 minutes, yielding 3.48%; and a solvent ratio of 1:30 w/v, yielding 3.48%.